Post-weaning social isolation increases ΔFosB/FosB protein expression in sex-specific patterns in the prelimbic/infralimbic cortex and hippocampus in mice. (1st January 2021) - Noback, Michael; Zhang, Gongliang; White, Noelle; Barrow, James C.; Carr, Gregory V.
Highlights: Post-weaning/adolescent social isolation increased ΔFosB in the cortex and hippocampus of adult mice. FosB was also increased in the cortex of isolated females. Short-term stress has persistent effects on the brain that depend on sex. Abstract: Social isolation is a growing public health concern across the lifespan. Specifically, isolation early in life, during critical periods of brain development, increases the risk of psychiatric disorders later in life. Previous studies of isolation models in mice have shown distinct neurological abnormalities in various regions of the brain, but the mechanism linking the experience of isolation to these phenotypes is unclear. In this study, we show that ΔFosB, a long-lived transcription factor associated with neuronal activity, chronic stress, and drug-induced neuroplasticity, is upregulated in the prelimbic/infralimbic (PL/IL) region of the cortex and hippocampus of adult C57BL/6J mice transiently isolated for two weeks post-weaning. Additionally, a related transcription factor, FosB, is also increased in the PL/IL in socially isolated females.In contrast, both ΔFosB and FosB are increased in male mice isolated for six weeks from weaning until tissue collection. These results show that short-term isolation during the critical post-weaning period has long-lasting and sex-dependent effects on gene expression in brain and that FosB/ΔFosB expression provides a potential mechanistic link between post-weaning social isolation and associated neurological abnormalities.